Analisis Pengaruh Transaction Security, E-Service Quality Dan E-Trust Terhadap Customer Loyalty Pada Pengguna Mobile Banking BRImo (Studi Kasus Mahasiswa Universitas Islam Malang Angkatan 2019) - Shoufil Fadilah; Ronny Malavia Mardani; Restu Millaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study is to quantify and evaluate the impact of transaction security, e-service quality, and e-trust on customer loyalty among BRImo mobile banking users. The strategy used is a quantitative strategy. Using this kind of purposeful sample study. 96 respondents who completed a questionnaire to calculate the slovin formula made up the sample for this study. Multiple linear regression analysis was the technique employed in this study for data analysis. Partial hypothesis testing (t-test) examines the data that were used. The results of his research show that transaction security and e-service quality partially have a significant effect on customer loyalty for BRImo mobile banking users, while e-trust partially has no significant effect on customer loyalty for BRImo mobile banking users. Keywords : Transaction Security, E-Service Quality, E-Trust, Customer Loyalty